2019
DOI: 10.1039/c9sm01123d
|View full text |Cite
|
Sign up to set email alerts
|

Many-chain effects on the co-nonsolvency of polymer brushes in a good solvent mixture

Abstract: The polymer brush normally swells in a good solvent, while it collapses in a poor solvent. An abnormal response of polymer brush, so-called co-nonsolvency, is a phenomenon where the brush collapses counter-intuitively in a good solvent mixture. In this work, the structural properties of the co-nonsolvency in the grafted polymers are investigated using molecular dynamics simulation. We consider the brushes at three different grafting densities to study the effect of topologically excluded volumes on the co-nons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 63 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…The reason behind this observation is that the grafting-to synthetic approach leads to much lower grafting densities for the high-molecular-weight polymers, see the second column of Table . This in turn leads to particular morphologies in the collapsed state such as octopus-shape micelles or collapsed globules, see the last column of Table . In turn, the hydrodynamic thickness variation of such sparsely grafted polymer layers displays only weak variation as compared with the dense brush regime.…”
Section: Resultsmentioning
confidence: 99%
“…The reason behind this observation is that the grafting-to synthetic approach leads to much lower grafting densities for the high-molecular-weight polymers, see the second column of Table . This in turn leads to particular morphologies in the collapsed state such as octopus-shape micelles or collapsed globules, see the last column of Table . In turn, the hydrodynamic thickness variation of such sparsely grafted polymer layers displays only weak variation as compared with the dense brush regime.…”
Section: Resultsmentioning
confidence: 99%
“…Parameter γ represents the bridging efficiency of the molecular matching between the monomer and cosolvent; for convenience but without losing generality, in this study, γ can be treated as a constant with a value of γ = 1 for the PNiPAAm/alcohol/water system. Direct evidences supporting this central assumption from molecular dynamic simulations ,, showed that a single chain can form loops because of preferential attraction between the polymer and cosolvent. In addition, experimental evidences supporting this central assumption come from a Raman spectroscopic study which investigated cononsolvency behaviors of linear poly­( N -isopropylacrylamide) polymers in methanol–water mixtures, in which methanol molecules aggregate into clusters and behave like temporal bridges between the polymer segments…”
Section: Extension Of the Adsorption-attraction Modelmentioning
confidence: 86%
“…Starting from solutions of linear homopolymers, the research on cononsolvency has been extended toward increasingly complex systems, such as cross-linked microgels, , diblock copolymer micelles, and grafted polymer brushes. This resulted in a number of applications of the effect across different fields of science. To name a few examples, the cononsolvency effect can be used for the capture and release of nanoparticles, , selective precipitation of DNA, force actuation, friction tuning, and the detection of volatile organic compounds .…”
Section: Introductionmentioning
confidence: 99%